Shape–function insights into bifunctional O-GlcNActransferase of Listeria monocytogenes EGD-e. (8th August 2020) - Choudhary, Pravinkumar; Badmalia, Maulik D; ,; Rao, Alka
Abstract: O -GlcNAcylation is an important post-translational modification of proteins. O -GlcNAcylated proteins have crucial roles in several cellular contexts both in eukaryotes and bacteria. O -GlcNActransferase (OGT) is the enzyme instrumental in O -GlcNAcylation of proteins. OGT is conserved across eukaryotes. The first bacterial OGT discovered is GmaR in Listeria monocytogenes . GmaR is a GT-2 family bifunctional protein that catalyzes glycosylation of the flagellin protein FlaA and controls transcription of flagellar motility genes in a temperature-dependent manner. Here, we provide methods for heterologous expression and purification of recombinant GmaR and FlaA, in vivo/in vitro glycosylation assays, analysis of the molecular form of recombinant GmaR and detailed enzyme kinetics. We study the structure and functional dynamics of GmaR. Using solution small-angle X-ray scattering and molecular modeling, we show that GmaR adopts an extended shape with two distinctly spaced structural units in the presence of cofactor Mg 2+ and with donor UDP-GlcNAc and cofactor combined. Comparisons of restored structures revealed that in-solution binding of Mg 2+ ions brings about shape rearrangements and induces structural-rigidity in hyper-variable regions at the N-terminus of GmaR protein. Taking function and shape data together, we describe that Mg 2+ binding enables GmaR to adopt a shape that can bind the substrate. The manuscript provides the first 3D solution structure of a bacterial OGT of GT-2 family and detailed biochemical characterization of GmaR to facilitate its future applications.